LINGKUNGAN KERJA BERPENGARUH TERHADAP KINERJA PEGAWAI DI DINAS PERPUSTAKAAN DAN ARSIP KABUPATEN TANGERANG - Galuh Lutfi Fadil; Yusmedi Yusuf; Seno Santoso (UNIVERSITAS ISLAM SYEKH YUSUF, 2019)
This research aims to describe and analyze The Influence of the Work Environment on Employee Performance in The Library and Archives Service in Tangerang District. The population in this study amounted to 48 respondents, the sampling technique used was the saturation sampling technique (census). Respondents in this study were the Library and Archives Service in Tangerang District. The research method used is a quantitative-associative method. Then the data were analyzed using the SPSS (Statistical Product and Service Solution) for windows version 21.0 using the correlation technique with the Pearson product moment method and then proceed with regression and hypothesis testing. The results in this study are